Penetapan Kadar Kalsium Pada Daun Kelor ( Moringa Oleifera L ) Metoda Permanganometri - Deni Fisnowita (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2023)
Moringa plant (Moringa Oleifera L) has many benefits for humans. All parts of this plant can be used. In the city of Padang, moringa plants thrive, but their use is limited and information on the content of moringa is still limited, so research is needed. The research objective was to determine calcium levels in Moringa leaves (Moringa Oleifera L). The method used to determine calcium levels is the Permanganometric method. Sampling was taken from the city of Padang. The results showed that the calcium levels in the leaves of Moringa (Moringa Oleifera L) permanganometrically obtained 0.3978%w/b.